Reduced Cancer Screening Due to Lockdowns of the COVID-19 Pandemic: Reviewing Impacts and Ways to Counteract the Impacts - Luu, Tuan (Frontiers in Oncology, 2022)
The COVID-19 pandemic has created disruptions in health services in general and cancer screening and diagnostic services in particular, leading to diminished cancer screening participation rates. This paper aims to seek insights into impacts that the pandemic has had on cancer screening, impacts that reduced cancer screening may have in the long run, and how to address such impacts. The paper demonstrates that reduced cancer screening in the pandemic is likely to result in enhanced demands for cancer screening in the new normal, enhanced demands for resources to address such demands, and poor prognosis due to stage migration of cancer diseases. Some measures are recommended for counteracting these impacts.